Mild heat stress promotes the differentiation of odontoblast-like MDPC-23 cells via yes-associated protein - Peiqi Liu; Zhen Li; Hui Zhang; Yijie Wang; Yuxin Liao; Yi Guo; Chenxu Wang; Yuanwu Zou; Rui Zou; Lin Niu (International Journal of Hyperthermia)
Purpose Dentin hypersensitivity (DH) is a prevalent condition, but long-term effective treatments are scarce. Differentiation of odontoblast-like cells is promising for inducing tertiary dentinogenesis and ensuring sustained therapeutic efficacy against DH. This study examined the effects and mechanism of action of mild heat stress (MHS) on the differentiation of odontoblast-like MDPC-23 cells.Methods We used a heating device to accurately control the temperature and duration, mimicking the thermal microenvironment of odontoblast-like cells. Using this device, the effects of MHS on cell viability and differentiation were examined. Cell viability was assessed using the MTT assay. The expression and nucleoplasmic ratio of the yes-associated protein (YAP) were examined by western blotting and immunofluorescence. The gene expression levels of heat shock proteins (HSPs) and dentin matrix protein-1 (DMP1) were measured using qPCR. Dentin sialophosphoprotein (DSPP) expression was evaluated using immunofluorescence and immunoblotting. Verteporfin was used to inhibit YAP activity.Results Mild heat stress (MHS) enhanced the odontoblast differentiation of MDPC-23 cells while maintaining cell viability. MHS also increased YAP activity, as well as the levels of HSP25 mRNA, HSP70 mRNA, HSP90α mRNA, DMP1 mRNA, and DSPP protein. However, after YAP inhibition, both cell viability and the levels of HSP90α mRNA, DMP1 mRNA, and DSPP protein were reduced.Conclusion YAP plays a crucial role in maintaining cell viability and promoting odontoblast differentiation of MDPC-23 cells under MHS. Consequently, MHS is a potential therapeutic strategy for DH, and boosting YAP activity could be beneficial for maintaining cell viability and promoting odontoblast differentiation.